Restriction fragment length polymorphism of genes of the alpha 2(XI) collagen, bone morphogenetic protein-2, alkaline phosphatase, and tumor necrosis factor-alpha among patients with ossification of posterior longitudinal ligament and controls from the Japanese population - Koga, H; Hayashi, K; Taketomi, E; Matsunaga, S; Yashiki, S; Fujiyoshi, T; Sonoda, S; Sakou, T (Spine (Philadelphia, Pa. 1976), 1996)
The present study analyzed the restriction fragment length polymorphism patterns of alpha 2(XI) collagen, bone morphogenetic protein-2, alkaline phosphatase, and tumor necrosis factor-alpha genes in patients with ossification of the posterior longitudinal ligament. This study investigates the genetic polymorphism of bone-induced factors in patients with ossification of the posterior longitudinal ligament and compares it with healthy control subjects. To clarify the genetic markers linked to ossification of the posterior longitudinal ligament. Ossification of the posterior longitudinal ligament is a genetic disease associated with abnormal calcium metabolism involving the posterior longitudinal ligament. Previous genetic studies have not identified the pathologic mechanism of ossification of the posterior longitudinal ligament. Histopathologic studies of ossification of the posterior longitudinal ligament and the animal model, the spinal hyperostotic mouse, have revealed an increase in Type XI collagen and bone morphogenetic protein-2 expression. Eighteen Japanese patients with ossification of the posterior longitudinal ligament and 51 healthy, unrelated control subjects were investigated for the restriction fragment length polymorphism patterns of COL11A2, bone morphogenetic protein-2, alkaline phosphatase, and tumor necrosis factor-alpha, genes with various restriction endonucleases. The gene frequencies of COL11A2 obtained with BamHl (10.0 kb fragment) and HindIII (19.0 kb fragment) observed in patients with ossification of the posterior longitudinal ligament were higher compared with control subjects (0.43 and 0.14, respectively). These differences were statistically significant (BamHl P = 0.018; Hindlll P = 0.046). Two new restriction fragment length polymorphism patterns were detected of the bone morphogenetic protein-2 gene with Mspl and Taql and one already known restriction fragment length polymorphism pattern of the tumor necrosis factor-alpha gene with Ncol. However, they were not significantly different from the control subjects. Seven restriction fragment length polymorphisms of COL11A2 gene were identified. Two of them (BamHl, 10.0/10.0 kb genotype; HindIII, 19.0/19.0 kb genotype) were significantly different in patients with ossification of the posterior longitudinal ligament.